Exploring pathways to participation in an at‐risk species conservation program. Issue 9 (27th July 2021) - Sorice, Michael G.; Donlan, C. Josh; Santo, Anna R.; Luque, Gloria M.; Hagen, Christian A.
Abstract: The success of conservation efforts for imperiled and endangered wildlife species relies on private landowners, yet a definitive model of landowner cooperation remains elusive. We use a case study to explore the multiple pathways by which demographics, rootedness, resource dependence, environmental attitudes, social influence, and program structure intersect to jointly explain participation in a federally funded cost‐share program to help prevent the Lesser Prairie‐Chicken from being listed under the U.S. Endangered Species Act. We conducted structured interviews across three ecoregions with 64 participants and 22 nonparticipants. We analyzed the data using fuzzy‐set qualitative comparative analysis, an approach that identifies the multiple combinations of conditions related to engagement in the program. We found that two concepts, landowner characteristics and social influence, were most commonly associated with participation while profiles representing typical landowner tropes performed poorly. Finally, the positive effect of encouragement by agency representatives suggests that agency staff play a central role in determining participation. It also suggests landowners' decision processes may not be as deliberative as the literature on private lands conservation suggests. The results of our case study suggest new avenues for research that explicitly consider the role of heuristics in decisions to participate. Abstract : We use a case study to explore private landowner participation in a federally funded cost‐share program to help prevent listing of the Lesser Prairie‐Chicken under the U.S. Endangered Species Act. We find that there are multiple pathways to participation and that this likely the norm rather than the exception.